2008
DOI: 10.1590/s0100-40422008000600008
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a continuous flow, integrated nebulizer-hydride generator for flame atomic absorption spectrometry

Abstract: Recebido em 17/4/07; aceito em 29/2/08; publicado na web em 13/8/08An evaluation of the performance of a continuous flow hydride generator-nebulizer for flame atomic absorption spectrometry was carried out. Optimization of nebulizer gas flow rate, sample acid concentration, sample and tetrahydroborate uptake rates and reductant concentration, on the As and Se absorbance signals was carried out. A hydrogen-argon flame was used. An improvement of the analytical sensitivity relative to the conventional bead nebul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Preliminary experiments suggested that a nebulizer provided the best transfer of generated CO 2 into the gas phase. Effective nebulizing typically needs a high gas flow rate/liquid flow rate ratio . In the present study, a micronebulizer (Figure S1), which required 10–50 mL/min of nebulizing gas for a solution flow of 0.80 mL/min, was developed.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary experiments suggested that a nebulizer provided the best transfer of generated CO 2 into the gas phase. Effective nebulizing typically needs a high gas flow rate/liquid flow rate ratio . In the present study, a micronebulizer (Figure S1), which required 10–50 mL/min of nebulizing gas for a solution flow of 0.80 mL/min, was developed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Effective nebulizing typically needs a high gas flow rate/liquid flow rate ratio. 27 In the present study, a micronebulizer (Figure S1), which required 10−50 mL/min of nebulizing gas for a solution flow of 0.80 mL/min, was developed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1 The most oen employed hydride atomizer for AF is a miniature diffusion ame (MDF) [2][3][4][5][6][7] but it can also be very useful for AA spectrometry. 4,8 An optimization of the atomization is required to reach an excellent performance of the whole procedure of element determination based on HG. Presently, the optimization of hydride atomization must be performed by the laborious trialand-error approach.…”
Section: Introductionmentioning
confidence: 99%
“…Compromised optimum values of the experimental parameters were identified using a response optimiser. The optimised conditions provided improved sensitivities for the hydride-forming elements compared with respective conventional nebulisation systems by factors of 67 (As) and 64 (Sb) for ICP-AES and 36 (As) and 56 (Sb) for ICP-MS. Murillo et al 81 evaluated the performance of their 'continuous flow hydride generator-nebuliser' for hydrogen-argon flame AAS. The accuracy of the system was checked against an oyster tissue SRM.…”
mentioning
confidence: 99%